Factors associated with universal infant free school meal take up and refusal in a multicultural urban community - Goodchild, G.A.; Faulks, J.; Swift, J.A.; Mhesuria, J.; Jethwa, P.H.; Pearce, Joanne (Wiley, 2017)
Background